Outcomes of a percutaneous coronary intervention versus coronary artery bypass grafting in octogenarians - Šerpytis, Rokas; Puodžiukaitė, Lina; Petrauskas, Saulius; Misonis, Nerijus; Kurminas, Mantas; Laucevičius, Aleksandras; Šerpytis, Pranas (Acta medica Lituanica, 2019)
Background. The data on long-term outcomes for elderly patients with coronary artery disease who undergo invasive treatment is limited. This study aimed to assess long-term outcomes and risk factors for patients over 80 years of age who underwent revascularisation. Methods. This single-centre retrospective study included ≥80-year-old patients who underwent coronary angiography between 2012 and 2014. Among 590 study patients, 411 patients had significant angiographic changes and had either a percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) performed. Baseline patient characteristics, including demographics, comorbidities, survival to hospital discharge, and long term mortality were analysed. Three-year mortality was assessed. Results. Three hundred sixty-nine (89.8%) patients underwent PCI and in 42 (10.2%) CABG was performed. Significant differences between groups were detected in heart failure (PCI – 51.2% vs. CABG – 78.6%; p = 0.001), previous CABG (11.4% vs. 0%; p = 0.014), cardiogenic shock (12.2% vs. 0%; p = 0.008). Hospital mortality rate in the PCI group – 10.6%, CABG – 7.1%; p = 0.787. A median 3-year survival rate in the PCI group – 66.1%, CABG – 66.7%; p = 1.000. Chronic heart failure (OR 2.442; 95% CI: 1.530–3.898, p < 0.001), atrial fibrillation (OR 0.425; 95% CI: 0.261–0.692, p < 0.001), cardiogenic shock (OR 0.120; 95% CI: 0.054–0.270, p = 0.001), and LMCA stenosis (OR 2.104; 95% CI: 1.281–3.456, p = 0.003) were identified as independent 3-year all-cause mortality predictors in multivariate regression analysis. Conclusions. There was no significant difference in hospital mortality and survival rates between elderly patients who underwent PCI or CAGB. The majority of elderly patients underwent a PCI and these patients appeared to experience cardiogenic shock more frequently.
Keywords: percutaneous coronary intervention; coronary artery bypass grafting; coronary artery disease; octogenarians